2000
DOI: 10.1016/s0928-8244(00)00202-9
|View full text |Cite
|
Sign up to set email alerts
|

Super-infection by Bacillus thuringiensis H34 or 3a3b can lead to death in mice infected with the influenza A virus

Abstract: Bacterial super-infections are the main cause of complication and mortality after influenza virus (IAV) infection. Since Bacillus thuringiensis (Bt) is considered non-pathogenic for humans and is widely sprayed in urban areas, the aim of this work was to evaluate the potential pathogenicity of a combined infection Bt-IAV in a mouse model of pneumonia. Bacteria used for super-infections were Bt serotype H34 isolated from human infection and the insecticidal strain 3a3b obtained from a commercial source. Virus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In addition, Locci (23) suggested that secondary bacterial infections, e.g., Staphylococcus aureus, GAS, group B streptococcus, Streptococcus pneumoniae, and Haemophilus influenzae, are closely associated with complications in influenza. Some groups of researchers have also found that infection with bacteria after IAV infection leads to the death of mice (11,14,17,22,24). In the present study, all mice infected with both IAV and GAS developed severe pneumonia (Fig.…”
Section: Vol 77 2003 Tsls Induced By Superinfection 4109supporting
confidence: 66%
“…In addition, Locci (23) suggested that secondary bacterial infections, e.g., Staphylococcus aureus, GAS, group B streptococcus, Streptococcus pneumoniae, and Haemophilus influenzae, are closely associated with complications in influenza. Some groups of researchers have also found that infection with bacteria after IAV infection leads to the death of mice (11,14,17,22,24). In the present study, all mice infected with both IAV and GAS developed severe pneumonia (Fig.…”
Section: Vol 77 2003 Tsls Induced By Superinfection 4109supporting
confidence: 66%
“…In contrast, many strains of the Bc group member Bacillus thuringiensis (Bt) are known to be entomopathic, and some of them have been developed for large-scale commercial use in forestry (e.g., against spruce budworm, gypsy moth), agriculture (e.g., against corn borer, tobacco budworm) and prevention of disease dissemination (e.g., against mosquitos, blackflies). However, there are reports that some Bt strains are infectious to humans, and similar in properties to Bc strains examined (Damgaard et al 1997; Hernandez et al 1998, 1999, 2000; Jackson et al 1995; McIntyre et al 2008; Samples and Buettner 1983). …”
Section: Introductionmentioning
confidence: 83%
“…The spores are associated with large crystal protein inclusions, which can make up to 25% of the dry weight of the spore preparations. In addition, like B. cereus, B. thuringiensis could be considered an opportunistic pathogen in animals and human [9][10][11]. Upon ingestion by insect larvae, the protoxin crystals solubilize in the mid-gut, where it is cleaved by a gut protease to produce an active toxin (d-endotoxins) of about 60 kDa.…”
Section: Bacillus Thuringiensismentioning
confidence: 99%
“…A few genes encoding cytotoxin K and non-hemolytic enterotoxin C subunit, amongst others, have only been found in B. cereus [47]. While one can only infer the pathogenicity of B. cereus ZK based on its isolation from a dead zebra, the opportunistic pathogenicity of B. thuringiensis 97-27 has been confirmed by infection of both immunosuppressed and immunocompetent mice [9][10][11]. Interestingly, a recent study showed that a fused PlcR-PapR construct was able to restore strong hemolytic activities when introduced in B. anthracis [59], indicating that these genes, while not upregulated, are still fully functional and have not undergone evolutionary decay.…”
Section: B Anthracis Genomic Analysis For Molecular and Forensic Epimentioning
confidence: 99%